I like to know if anyone can tell me if my answer is correct.
Suppose f is an invertible function from Y to Z and g is an invertible function from X to Y. Show that the inverse of the composition is f o g is given by (f o g)-1 = g-1 o f -1
f –1(z) = y, g-1(y) =x
(f o g)-1(y) = f -1 (g(y))-1 =x
(g-1 o f -1)(y) = g-1(f(y))-1= z
Therefore, (f o g)-1 = g-1 o f -1 are not equal. In other words, the commutative law does not hold for the composition function.
(The f -1 and g-1 stands for the power of -1, sorry i don't have the button function to purt it correctly)